Perspektif Hukum Pembebanan Hak Tanggungan Atas Sertifikat Hak Milik Satuan Rumah Susun Sebagai Jaminan Kredit Perbankan: Legal Perspective Encumbrance Right Mortgage on Certificate of Ownership Right Flat Units as Banking Credit Guarantee - Khaidir Nasution; Ahmad Fauzi; Ramlan Ramlan (Universitas Medan Area, 2022)
This study discusses the legal arrangements on land that are charged with mortgage rights to flats standing on the land, then analyzes the imposition of certificates of ownership rights to flats as collateral for bank credit and to find out the implementation of execution if one of the debtors breaks their promises related to the granting of mortgage rights to the flats. used as collateral for bank loans. The research empirical juridical type, namely research that emphasizes the use of legal norms in writing and is supported by data collected in the field and the results of interviews with sources and informants as supporting data. Based on the results the ownership rights of the apartment unit are simultaneous or concurrent in nature which contains joint rights and individual rights. The right of ownership of the apartment unit itself can be charged with mortgage rights as collateral for bank credit based on article 47 paragraph (5) of the Flats Law. Execution of the ownership rights of the apartment unit that is charged with mortgage rights as credit guarantees as a result of the debtor defaulting to the creditor, then the bank as the creditor of the Flats Unit does not directly execute the Mortgage on the creditor guarantee but the bank will take persuasive steps as well as non-litigation mediation to resolve non-performing loans so that no party feels aggrieved and if the non-litigation process reaches a dead end, then the litigation process is carried out.